Thermodynamic and Surface Properties of Ni-Si-Fe-Mo in Molten State: A Theoretical Study - Sah, Dipendra Kumar; Mehta, Upendra; Adhikari, Devendra; Yadav, Sashit Kumar (Journal of Nepal Physical Society, 2024)
The integral excess free energy of mixing of Ni-Si-Fe-Mo quaternary alloy was calculated at temperatures of 2700 K, 2800 K, 2900 K and 3000 K using the General Solution Model. The excess Gibbs free energy of mixing for the constituent binary subsystems was calculated in the framework of Redlich-Kister polynomial. The self-consistent thermodynamic parameters for the respective thermodynamic function were taken from the available literature data. Surface tension of the system and surface concentrations of its components were calculated in the framework of Butler’s model using the determined values of partial excess free energy of each component. The activity of components increased with the rise in temperature of the system. The negative value of integral excess Gibbs free energy of mixing and surface tension of the system decreased linearly at elevated temperatures